2022
DOI: 10.4081/jbr.2022.10632
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of N-acetylcysteine on aluminum phosphide toxicity in rats

Abstract: Aluminum Phosphide (ALP) is one of the most dangerous pesticides. When it comes into contact with water, it emits Phosphine (PH3) gas, which causes poisoning and death in many people. The purpose of this study is to look into the role of N-acetylcysteine in the treatment of aluminum phosphide toxicity in rats. In this study, 30 male Wistar rats were fed with aluminum phosphide orally. After 15 minutes, N-acetylcysteine was administered intraperitoneally. The antioxidant enzymes glutathione S-Transferase (GST),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Oxidative stress and the production of free oxygen radicals (ROS) mediate the mechanism of phosphine toxicity; therefore, using antioxidants such as N-acetylcysteine, glutathione, melatonin, vitamin C, vitamin E and carotenes [2] may be beneficial and limit toxicity [6]. Experiments in rats concluded that N-acetylcysteine reduces phosphideinduced myocardial oxidative damage [6], replenishing cellular glutathione [14,25,37], and improves hepatic manifestations and prevents hepatic necrosis [2]. In 2018, a case where a woman was poisoned with zinc and aluminum phosphide was reported; she survived due to treatment based on NAC, digoxin and insulin [6,38].…”
Section: Antioxidantsmentioning
confidence: 99%

Zinc Phosphide Poisoning: From A to Z

Juárez-Martínez,
Madrigal-Anaya,
Rodríguez-Torres
et al. 2023
Toxics
“…Oxidative stress and the production of free oxygen radicals (ROS) mediate the mechanism of phosphine toxicity; therefore, using antioxidants such as N-acetylcysteine, glutathione, melatonin, vitamin C, vitamin E and carotenes [2] may be beneficial and limit toxicity [6]. Experiments in rats concluded that N-acetylcysteine reduces phosphideinduced myocardial oxidative damage [6], replenishing cellular glutathione [14,25,37], and improves hepatic manifestations and prevents hepatic necrosis [2]. In 2018, a case where a woman was poisoned with zinc and aluminum phosphide was reported; she survived due to treatment based on NAC, digoxin and insulin [6,38].…”
Section: Antioxidantsmentioning
confidence: 99%

Zinc Phosphide Poisoning: From A to Z

Juárez-Martínez,
Madrigal-Anaya,
Rodríguez-Torres
et al. 2023
Toxics